FRI0442 Long-term treatment with rituximab in interstitial lung disease related to systemic sclerosis: our clinical experience. (12th June 2018) - Lumetti, F.; Spinella, A.; Ariani, A.; Cocchiara, E.; Colaci, M.; Silva, M.; Sverzellati, N.; Ferri, C.; Salvarani, C.; Giuggioli, D.
Abstract : Background: Systemic sclerosis (SSc) is an immune-mediated disorder characterised by abnormal fibrosis and diffuse microangiopathy with skin and internal organ involvement. Interstitial lung disease (ILD) represents one of the most challenging complication of SSc, difficult to manage and correlate with a poor prognosis. Chest Computed Tomography (CT) is the gold standard for detection and evaluation of SSc-ILD by means of semi-quantitative scoring of extent of lung involvement. Some preliminary data suggest that rituximab (RTX) may be usefully employed in the treatment of SSc patients. Objectives: To investigate the role and effect of RTX on ILD in our SSc patients' series. Methods: We retrospectively evaluated a series of 18 SSc patients (M/F 6/12, mean age 54.6±17.6 SD years, mean disease duration 11.4±6.5 SD years, L/D cutaneous subsets 6/12) who received one or more cycles of RTX (4 weekly infusions of 375 mg/m2) every 6 months for a total of 1–6 cycles. Lung involvement was studied by means of pulmonary function tests (PFTs) (18/18) and inspiratory chest CT (10/18) before and after treatment. In particular, we considered PFTs performed 6 months before RTX, at time 0, one year after the first RTX cycle, and at the end of follow-up (13.7±7.3 years). ILD extent score was assessed by the semi-quantitative method proposed by Goh et al (2008). 1 Results: Forced vital capacity (FVC%) significantly reduced during the year before RTX treatment [from 95.2±17.4 to 84.8±16.4; p=0.0017], as well as the diffusing capacity for carbon monoxide (DLCO%) [from 58.1±14.3 to 47.6±12.9; p=0.0002]. Conversely, FVC% and DLCO% stabilised one year after the first RTX cycle (80.8±23 and 47.8±15.7, respectively), and at the end of the follow-up (84.3±24.6 and 54.8.8±12.3, respectively; p=0.0001). In our cohort, only 7/10 patients had ILD detectable on CT before treatment. At the end of the follow-up we observed that ILD extented in 6/7 cases one patient remained stable, the three subjects without ILD did not developed pulmonary fibrosis. Conclusions: According to PFTs results, our study showed that RTX could stabilise the progression of lung function tests in SSc patients. However, the semi-quantitative visual score identified radiological pulmonary worsening in many patient with stabilised PFTs. Therefore, the correlations between functional and radiological outcomes are so weak that many Authors suggested they should be considered together in SSc-ILD assessment. Reference: [1] Goh NSL, Desai SR, Veeraraghavan S, et al. Interstitial lung disease in systemic sclerosis: a simple staging system. Am J Respir Crit Care Med2008;177:1248–54. Disclosure of Interest: None declared